Critical Care Management Following Lung Transplantation - Kyeongman Jeon (Journal of Chest Surgery, 2022)
Postoperative critical care management for lung transplant recipients in the intensive care unit (ICU) has expanded in recent years due to its complexity and impact on clinical outcomes. The practical aspects of post-transplant critical care management, especially regarding ventilation and hemodynamic management during the early postoperative period in the ICU, are discussed in this brief review. Monitoring in the ICU provides information on the patient’s clinical status, diagnostic assessment of complications, and future management plans since lung transplantation involves unique pathophysiological conditions and risk factors for complications. After lung transplantation, the grafts should be appropriately ventilated with lung protective strategies to prevent ventilator-induced lung injury, as well as to promote graft function and maintain adequate gas exchange. Hypotension and varying degrees of pulmonary edema are common in the immediate postoperative lung transplantation setting. Ventricular dysfunction in lung transplant recipients should also be considered. Therefore, adequate volume and hemodynamic management with vasoactive agents based on their physiological effects and patient response are critical in the early postoperative lung transplantation period. Integrated management provided by a professional multidisciplinary team is essential for the critical care management of lung transplant recipients in the ICU.